2012
DOI: 10.1111/napa.12001
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Phenomena and the Syndemic Factor: Substance Abuse, Violence, Hiv, and Depression Among Hispanic Women

Abstract: Researchers exploring the health of Hispanics in South Florida utilizing a combination of qualitative and quantitative research methods have identified that substance abuse, violence, risky sexual behavior, and depression are not only conceptualized as tightly interrelated health and social problems, but also hold together in a measurement model to represent an underlying phenomenon (i.e., the Syndemic Factor). The purpose of this study is to test hypothesized relationships between cultural phenomena and the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 51 publications
(80 reference statements)
7
22
3
Order By: Relevance
“…Education and acculturation were related to the syndemic factor among Hispanic women, supporting previous syndemic theory research identifying the important role that socioeconomic and cultural factors play in influencing syndemic risks (Gonzalez-Guarda et al, 2011; Gonzalez-Guarda et al, 2012; Koblin et al, 2015 (Koblin et al, 2015). However, unlike previous research which has documented the protective effects that maintaining Hispanic culture (Hispanicism) has on the syndemic factor (Gonzalez-Guarda et al, 2012), both Hispanicism and Americanism were positively related to the syndemic factor.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Education and acculturation were related to the syndemic factor among Hispanic women, supporting previous syndemic theory research identifying the important role that socioeconomic and cultural factors play in influencing syndemic risks (Gonzalez-Guarda et al, 2011; Gonzalez-Guarda et al, 2012; Koblin et al, 2015 (Koblin et al, 2015). However, unlike previous research which has documented the protective effects that maintaining Hispanic culture (Hispanicism) has on the syndemic factor (Gonzalez-Guarda et al, 2012), both Hispanicism and Americanism were positively related to the syndemic factor.…”
Section: Discussionsupporting
confidence: 80%
“…Risk factors included socioeconomic disadvantage, the percent of their lifetime they had lived in the U.S., and acculturation as risk factors. Conversely, family support and the maintenance of Hispanic practices such as the reliance of Spanish in communications with family and friends were identified as being protective (Gonzalez-Guarda, McCabe, Vermeesch, Cianelli & Peragallo, 2012). …”
Section: The Sava Syndemicmentioning
confidence: 99%
“…It is important to note that traditional gender role attitudes are not exclusively associated with Latino culture; studies of violence conducted with predominantly White or Caucasian samples have shown similar results (Anderson et al 2004;Santana et al 2006;Silverman and Williamson 1997). These findings support evidence that cultural factors among Latinos, specifically acculturation (Caetano et al 2004;Gonzalez-Guarda et al 2012) as reflected in greater orientation to U.S. values and traditional gender role attitudes (Falconier 2013;Reed et al 2011;Santana et al 2006), can be risk factors for intimate partner violence. However, much of what is known about the influence of these cultural factors on intimate partner violence has been derived from adult Latino samples.…”
Section: Discussionsupporting
confidence: 67%
“…Acculturation and traditional gender role attitudes are cultural variables that have been associated with greater risk of intimate partner violence among Latino 1 youth (Dardis et al 2015;Sabina et al 2016;Vagi et al 2013). However, intimate partner violence research on Latinos has drawn primarily from college-based (Coker et al 2008;Ramirez 2007) or adult (Caetano et al 2004;Cunradi 2009;Gonzalez-Guarda et al 2012) samples, lacked the inclusion of both victimization and perpetration outcomes, or been limited by cross-sectional studies (Ferguson 2011;Garcia et al 2005).…”
Section: Acculturation Traditional Gender Role Attitudes and Violencementioning
confidence: 94%
“…These findings are important in the context of racial and ethnic disparities in health because minorities often report more exposure to chronic and acute stress than do non-Hispanic Whites (Jackson et al 2010). Among Hispanics, experiences of stress may be related to identification or perceived identification with a socially marginalized group (González-Guarda et al 2012). Cervantes et al (2012) identified eight domains of stress among Hispanic adolescents that broadly describe cultural-related stressors, such as acculturative gap stress, immigration stress, and discrimination, and social stressors, such as negative experiences in the educational system, economic hardship, substance use, and community and gang violence (Cervantes et al 2012; Morales et al 2002).…”
Section: Stress and Us Hispanicsmentioning
confidence: 99%